Strategic approach to the planning of promotional activities - Cogoljević Vladan (Trendovi u Poslovanju, 2019)
Commercial propaganda has a long history, it has been used for different purposes and for different goals, but its implementation has always achieved good results in influencing the target audience. Commercial propaganda is the "most visible" marketing activity of the company. In today's market economy, a strategic approach to planning commercial propaganda as an instrument of the promotional mix is necessary. When planning propaganda activities, the starting point is to analyze the environment in which the company performs its business activity and the potential of the company, i.e. capabilities and limitations. Based on that analysis, it is possible to define the real goals of the company and therefore the marketing goals. The aim of this paper is to point out the importance of planning in commercial propaganda, which is manifested primarily in the elimination of spontaneity and influences the control of promotional activities.